Impact of noninvasive positive-pressure ventilation in unplanned extubation - (:unkn) unknown (Springer International Publishing, 2016)
Intubations are among the most common invasive interventions performed in the intensive care unit (ICU), and most ICU patients who require mechanical ventilation are intubated. Unplanned extubation (UE), an intubation-associated complication, is defined as the removal of an endotracheal tube by a patient or its accidental removal. The reported frequency of UE ranges between 3 and 16 % among patients on mechanical ventilatory support [1–3]. A previous study in our center showed a similar rate of extubation (11 %) [4]. Among its main causes are inadequate sedation and insufficient nursing care during positioning. Nevertheless, UE may occur even under optimal conditions where sedation is adequate and all necessary precautions are taken. Successful management of UE may result in shortened duration of intubation and reduced rate of complications associated with mechanical ventilation. On the other hand, failure to do so may lead to the need for reintubation, leading to an increased risk of complications. © Springer International Publishing Switzerland 2016.
Keywords: Noninvasive ventilation; Unplanned extubation